Effect of Cement Asphalt Mortar Debonding on Dynamic Properties of CRTS II Slab Ballastless Track - Ping Wang; Hao Xu; Rong Chen (Advances in Materials Science and Engineering)
The debonding of cement emulsified asphalt mortar (CA mortar) is one of the main damage types in China railway track system II slab ballastless track. In order to analyze the influence of mortar debonding on the dynamic properties of CRTS II slab ballastless track, a vertical coupling vibration model for a vehicle-track-subgrade system was established on the base of wheel/rail coupling dynamics theory. The effects of different debonding lengths on dynamic response of vehicle and track system were analyzed by using the finite element software. The results show that the debonding of CA mortar layer will increase the dynamic response of track. If the length of debonding exceeds 1.95 m, the inflection point will appear on the vertical displacement curve of track. The vertical vibration acceleration of slab increases 4.95 times and the vertical dynamic compressive stress of CA mortar near the debonding region increases 15 times when the debonding length reaches 3.9 m. Considering the durability of ballastless track, once the length of debonding reaches 1.95 m, the mortar debonding should be repaired.